Sonic Agency - LaBelle, Brandon (Goldsmiths Press, 2023)
In a world dominated by the visual, could contemporary resistances be auditory? Sonic Agency highlights sound’s invisible, disruptive and affective qualities, and asks whether the unseen nature of sound can support a political transformation.